Five new, microendemic Asian Leaf-litter Frogs (Leptolalax) from the southern Annamite mountains, Vietnam - Rowley, Jodi J. L.; Tran, Dao T. A.; Le, Duong T. T.; Dau, Vinh Q.; Peloso, Pedro L. V.; Nguyen, Truong Q.; Hoang, Huy D.; Nguyen, Tao T.; Ziegler, Thomas (Zootaxa, 2016)
The Leptolalax applebyi group of Asian leaf-litter frogs currently comprises four species of particularly small-bodied (<40 mm SVL) species distributed in the Central Highlands of Vietnam and northeastern Cambodia. In addition to their small size, the group is characterized by their morphological and genetic similarities, as well as their breeding habitat at headwaters of small mountain streams and seeps. A recent study suggested that at least two-thirds of the diversity of the group remained hidden within morphologically cryptic lineages. We expand upon the molecular, morphometric, and acoustic data and formally delineate and describe five of these lineages as distinct species: Leptolalax ardens sp. nov., Leptolalax kalonensis sp. nov., Leptolalax pallidus sp. nov., Leptolalax maculosus sp. nov., and Leptolalax tadungensis sp. nov. Due to habitat loss, the current ranges of these species are likely to be a fraction of their historical extent and under continued threat from deforestation.